PENGARUH JENJANG KARIR TERHADAP MOTIVASI DAN KINERJA KARYAWAN BANK - Joko Suyono (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
This study aims to prove and analyze the influence of work stress and career path towards employee motivation of Bank Jatim Surabaya, then to prove and analyze the influence of work stress and career path towards the performance of employees of Bank Jatim Surabaya, and to prove and analyze the influence of work motivation on employee performance Bank Jatim Surabaya. This study uses the method of causal study. The population used is 75 employees of Bank Jatim Surabaya. The data were collected by observing and distributing questionnaires. The analysis tool used is Structural Equation Modeling (SEM) with Smart PLS software (Partial Least Square). The results of this study indicate that (1) work stress negatively affect the Motivation of Employee at Bank Jatim Branch Surabaya; (2) Working stress affecting the performance of employees of Bank Jatim Surabaya Branch; (3) Career Level affect the Work Motivation on the employee of Bank Jatim Surabaya Branch; (4) Career Level Affects the Performance of Bank Jatim Surabaya Branch Officers; (5) Working Motivation Affects Performance at employees of Bank Jatim Surabaya Branch.